2005
DOI: 10.1097/01.cnd.0000176974.61136.45
|View full text |Cite
|
Sign up to set email alerts
|

Primary Lateral Sclerosis

Abstract: : Our experience supports the observation that PLS progresses more slowly than other forms of acquired motor neuron disease, particularly amyotrophic lateral sclerosis. Follow-up data suggest that patients with active denervation changes develop greater disability.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
29
0
1

Year Published

2007
2007
2017
2017

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 47 publications
(30 citation statements)
references
References 20 publications
0
29
0
1
Order By: Relevance
“…However, from the existing pathological data, PLS tends to affect the precentral gyrus or primary motor cortex and may show a decreased number of Betz cells. 1 Comparatively, PLS appears to involve the primary motor cortex more so than pure ALS. 10 Neuroimaging studies have confirmed selective vulnerability of the primary motor cortex.…”
Section: Commentmentioning
confidence: 99%
See 1 more Smart Citation
“…However, from the existing pathological data, PLS tends to affect the precentral gyrus or primary motor cortex and may show a decreased number of Betz cells. 1 Comparatively, PLS appears to involve the primary motor cortex more so than pure ALS. 10 Neuroimaging studies have confirmed selective vulnerability of the primary motor cortex.…”
Section: Commentmentioning
confidence: 99%
“…Clinical presentation and disease course are characterized by slowly progressive symptoms ranging from bulbar dysfunction, spastic dysarthria, dysphagia, and emotional lability to corticospinal tract findings such as limb weakness with spasticity. 1 Pure PLS represents a more benign neurodegenerative condition thought to affect only upper motor neurons and is characterized with a better prognosis than amyotrophic lateral sclerosis (ALS). 2 For the clinician, PLS is a challenging diagnosis because it can mimic several disorders such as Parkinson disease, multiple systems atrophy, corticobasal syndrome, 3 neurofilament inclusion body disease, 4 and hereditary spastic paraplegia.…”
Section: Rimary Lateral Sclerosismentioning
confidence: 99%
“…In addition, fluid-attenuated inversion recovery (FLAIR) images were slightly more sensitive in detecting CST signal alterations than T1w or T2w images (see Grosskreutz and colleagues for a review) [Grosskreutz et al 2008]. Also for the diagnosis of primary lateral sclerosis (PLS), MRI signs are described, that is, abnormalities (atrophy) in the precentral gyrus region and CST hyperintensities [Singer et al 2007]. In ALS and PLS, changes in the corpus callosum were described at individual and group level (see below).…”
Section: Diagnostic Role Of Neuroimaging In Motor Neuron Diseasesmentioning
confidence: 99%
“…Формы с преимущественным поражением верхнего мотонейрона. ПБС характеризуется изолированным поражением только верхнего мотонейрона в течение как минимум 4 лет после начала болезни [33,34]. Дан-ному варианту в отечественной классификации соот-ветствует высокая форма БАС.…”
Section: том 7 Volunclassified